Análise espectral dos autômatos celulares elementares - Ruivo, Eurico Luiz Prospero (2012)
The Fourier spectra of cellular automata rules give a characterisation of the limit configurations generated by them at the end of their time evolution. In the present work, the Fourier spectra of each rule of the elementary cellular automata rule space are computed, under periodic and non-periodic boundary conditions, and the space is then partitioned according to the similarity among these computed spectra, what gives the notion of spectral classes in such space. For the partition obtained under periodic boundary condition, each spectral class is analysed in terms of the behaviour of each of its rules and how this behaviour affects the correspondent spectrum. Finally, the spectral classes are related in terms of the similarity among them, for both boundary conditions, what results in graphs depicting the proximity among the spectral classes.